The Resistance Movement in Latvia during the Nazi German Occupation (1941–1945): Research Problems and Achievements - Neiburgs, Uldis (Genocidas ir rezistencija, 2008)
Unlike their counterparts in the majority of Western European states, where the recovery of their national freedom could be achieved along with the defeat of Hitler’s Germany, members of the Latvian resistance movement were forced to work under much more difficult conditions when struggle against one occupying power did not directly lead to the restoration of their sovereignty, this struggle taking place under the threat of the return of the other occupation rule. In the situation when the weakening of the Nazi Germany’s armed forces in their fight against the Soviet Union was not in the interests of the resistance movement. Part of this movement did participate in military reconnaissance and the collection of weapons and ammunition. The majority of its members were engaged in the dissemination of oral and written information, hampering the execution of the orders of the occupation rule. They tried to use their positions in the interests of the Latvian people by consolidating public commitment to a free and independent state of Latvia.
Keywords: Latvia; German occupation; resistance